White Nationalism, Politically Motivated Reasoning and Americans’ Attitudes About Criminally Charging Donald Trump - Sloan, Melissa Marie (The British journal of criminology, 2024)
On 19 December 2022, the United States House Select Committee referred former president Donald Trump to the Department of Justice for criminal prosecution. Subsequently, Mr. Trump was indicted four times and charged with 91 felonies. Nevertheless, some Americans have remained steadfast in supporting him. Observers theorize that indifference to Mr. Trump’s wrongdoing reflects white nationalism and politically motivated reasoning. We test this theory using experimental data from a national survey fielded before any public hearings or charges. Our analyses reveal that Americans who endorse white nationalism and those who hold right-wing political views are more likely to oppose criminal charges. Furthermore, the relationship between white nationalism and attitudes about criminally charging Mr. Trump is indirect, through identification with the political right.